A line spectrum detector based on improved coherent power spectrum estimation. Issue 1 (July 2021) - Feng, Song; Jiang, Keyu; Kong, Xiaopeng
Abstract: The line spectrum detection method based on coherent power spectrum estimation is one of the important research directions of weak signal line spectrum detection. For the purpose of resolving the problem of phase compensation inaccurate introduced by limited frequency search accuracy with the existing coherent power spectral estimate method, a modified line spectrum detector is proposed. The zero padding is used to improve the line spectrum frequency search accuracy in discrete Fourier transform (DFT) for phase compensation calculations, thereby obtaining more accurate line spectrum frequencies and phase compensation, which further improves Line spectrum detection performance. The detection performances of three detections based on Welch's method, coherently averaged power spectral estimate(CAPSE) and modified method are compared each other by computer simulations. The results show modified line spectrum detection can obtain a gain of 2-3dB, which verifies the effectiveness of the modified method.